Genome sequence and characterization of Streptomyces phage Pablito, representing a new species within the genus Janusvirus - Ongenae, Véronique; Azeredo, Joana; Kropinski, Andrew M.; Rozen, Daniel; Briegel, Ariane; Claessen, Dennis (Scientific reports, 2022)
Streptomycetes are ubiquitous soil bacteria. Here we report the complete and annotated genome sequence and characterization of Streptomyces phage Pablito, isolated from a soil sample in Haarlem, the Netherlands using Streptomyces lividans as host. This phage was able to infect a diverse range of Streptomyces strains, but none belonging to the sister genus Kitasatospora . Phage Pablito has double-stranded DNA with a genome length of 49,581 base pairs encoding 76 putative proteins, of which 26 could be predicted. The presence of a serine integrase protein indicated the lysogenic nature of phage Pablito. The phage remained stable over a wide range of temperatures (25–45 °C) and at pH ≥ 7.0, but lost infectivity at temperatures above 55 °C or when the pH dropped below 6.0. This newly isolated phage is closely related to Streptomyces phage Janus and Hank144 and considered a new species classified in the genus Janusvirus , within the subfamily Arquattrovirinae .